2011
DOI: 10.1021/jp1112125
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Interfacial Transport of Water in Nafion

Abstract: Water absorption, membrane swelling, and self-diffusivity of water in 1100 equivalent weight Nafion were measured as functions of temperature and water activity. Free volume per water at 80 °C, determined from water uptake and volume expansion data, decreases with water content in the membrane from 12 cm(3)/mol at λ = 0.5 H(2)O/SO(3) to 1.5 cm(3)/mol at λ = 4. The change in free volume with water content displays a transition at λ = 4. Limiting water self-diffusivity in Nafion was determined by pulsed gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
262
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(306 citation statements)
references
References 49 publications
32
262
1
1
Order By: Relevance
“…It shows that there are some differences among the values measured by different researchers and methods. However, the order of magnitude of d I I for Na + is about 1 × 10 −10 (m 2 /s), 41,42 and that of d W W is about 3 × 10 −10 (m 2 /s) 39,[43][44][45] in saturated Na + type Nafion-117 membrane.…”
Section: B Improved Np Equation Modelmentioning
confidence: 94%
“…It shows that there are some differences among the values measured by different researchers and methods. However, the order of magnitude of d I I for Na + is about 1 × 10 −10 (m 2 /s), 41,42 and that of d W W is about 3 × 10 −10 (m 2 /s) 39,[43][44][45] in saturated Na + type Nafion-117 membrane.…”
Section: B Improved Np Equation Modelmentioning
confidence: 94%
“…It has been shown that the interfacial mass-transfer coefficient for water transport can be significant relative to the transport coefficient, especially for drier membranes. 27,[93][94][95][96][97][98][99][100] Only a few models assume non-equilibrium and incorporate interfacial resistance for species transport. [101][102][103] To explore this effect in more detail, the baseline value adopted from Kientiz et al 27 and reported in Table VI was reduced by factors of 10 (×0.1) and 20 (×0.05) as shown in Figure 7 (and in Figure S8 of the SI).…”
Section: Impact Of Catalyst-layer Thickness-as Shown Inmentioning
confidence: 99%
“…55 Interestingly, Zhao et al 55 reported RH-independent interfacial resistance whereas Kienitz et al, 56 reported a decrease in mass-transport coefficient with increasing RH.…”
Section: -55mentioning
confidence: 99%